Recurrent Neisseria cinerea bacteremia secondary to cardiovascular implantable electronic device infection - Zachary S. Bernstein; James J. Vaillant; Hector I. Michelena; Sorin V. Pislaru; Daniel C. DeSimone (IDCases, 2023)
We present the first case of cardiac implantable electronic device (CIED) infection due to Neisseria cinerea in a 64-year-old woman from Panama. She had a history of splenectomy, aortic valve stenosis requiring transcatheter aortic valve replacement (TAVR), and permanent pacemaker placement. She presented with relapsing N. cinerea bacteremia over a 3-month period. Transesophageal echocardiography revealed a lead vegetation in the superior vena cava. She was successfully treated with pacemaker removal and 2 weeks of IV antibiotic therapy. N. cinerea is an aerobic gram-negative commensal diplococcus typically found in the human nasopharynx. Infection in humans is rare with few case reports in the literature.